Four proclamatory confrontations in scribal refraction - Brueggemann, Walter (Scottish journal of theology, 2003)
This paper offers a reflection upon the current preaching crisis in those parts of the United States church where old assumptions about preaching authority have collapsed. While preachers may have models of great confrontational authority available, in fact such authority for confrontation through preaching has largely evaporated. This paper explores new developments in OT studies that are related to canonical formulation, namely, that the biblical text as we have it is an outcome of belated editorial work whereby the text was reshaped with theological intentionality by scribes, a generative force in Judaism that transposed powerful memories into texts. Consequently, the great texts of confrontation between prophet and king, between truth and power, no longer offer dramatic confrontations but rather offer textual reflections upon remembered and perhaps constructed confrontations. The practical implication for preaching from this insight is that the preacher is not and need not be a player in confrontation as a prophet, but rather may be a scribe who keeps old texts available whereby the baptismal community may imagine its life differently. Four texts are considered wherein remembered dramatic confrontations have become textual resources.